Letter from Campbell Morfit to James Curtis Booth, May 24, 1852 - Morfit, Campbell (1852)
Campbell Morfit (1820-1897), a distinguished chemist and co-editor with James Curtis Booth (1810-1888) of the Encyclopedia of Chemistry (1850), writes to Booth to complain about an unforeseen chemical reaction.
Keywords: Booth, James Curtis, 1810-1888; Morfit, Campbell, 1820-1897